The Effect of Service Quality, Price, and Trust on Consumer Purchasing Decisions at Amarta Shop, Ponorogo Regency - Shiddiqi , Dzikri Ash; Sumarsono, Tanto Gatot; Khouroh , Umu (Science Tech Group, 2025)
Complex business competition in the modern era encourages every business actor to adapt a lot to their environment. One of them is by providing maximum service, both physically and online. Amarta Shop, Ponorogo Regency is the object of this research, to measure the quality of service obtained by consumers. The method used in this research is descriptive qualitative, by distributing questionnaires to obtain primary data that supports the results of this study. The results of this study indicate three things, namely (1) service quality affects consumer purchasing decisions, (2) competitive prices also encourage loyalty from consumers, so that in this aspect the Amarta store must pay attention to responsiveness, empathy and build trust with consumers. (3) The price aspect encourages loyalty from consumers, so the Amarta Store shows a good perception in the price aspect. From these three aspects, it shows that the service quality aspect has an influence on consumer decision making, the price aspect also shows influence, as well as the trust aspect.